2022
DOI: 10.1038/s41467-022-31909-w
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-induced spin polarization in a single magnetic molecule junction

Abstract: Many spintronic devices rely on the presence of spin-polarized currents at zero magnetic field. This is often obtained by spin exchange-bias, where an element with long-range magnetic order creates magnetized states and displaces the hysteresis loop. Here we demonstrate that exchange-split spin states are observable and usable in the smallest conceivable unit: a single magnetic molecule. We use a redox-active porphyrin as a transport channel, coordinating a dysprosium-based single-molecule-magnet inside a grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…In all the complexes, the ReO 4 À counter anion connects two [Mn(X-sal 2 -323)] + cationic units via N-HÁ Á ÁO(ReO 4 À ) interactions to form 1D supramolecular chains in 27, 28, and 30; 2D supramolecular chains in 29 and 3D supramolecular architecture in 31 respectively. This study showed the gradual but complete (27,31), abrupt and complete spin transition (28), gradual and incomplete (30), and an incomplete and sharp transition (29), owing to the structural effect (cooperativity, structural matrix) dominating the electronic effect coming from various substituents (Cl, Br, and NO 2 ). Furthermore, the introduction of electron-withdrawing groups at the 3,5 positions of the salicylaldehyde moiety decreased the p-donor ability and influenced the spin transition temperature in the order of T 1/2 (27) B T 1/2 (28) 4 T 1/2 (29) B T 1/2 (30) 4T 1/2 (31) (Fig.…”
Section: Stimuli-responsive Spin State Switching In Mn(iii) Systemsmentioning
confidence: 77%
See 1 more Smart Citation
“…In all the complexes, the ReO 4 À counter anion connects two [Mn(X-sal 2 -323)] + cationic units via N-HÁ Á ÁO(ReO 4 À ) interactions to form 1D supramolecular chains in 27, 28, and 30; 2D supramolecular chains in 29 and 3D supramolecular architecture in 31 respectively. This study showed the gradual but complete (27,31), abrupt and complete spin transition (28), gradual and incomplete (30), and an incomplete and sharp transition (29), owing to the structural effect (cooperativity, structural matrix) dominating the electronic effect coming from various substituents (Cl, Br, and NO 2 ). Furthermore, the introduction of electron-withdrawing groups at the 3,5 positions of the salicylaldehyde moiety decreased the p-donor ability and influenced the spin transition temperature in the order of T 1/2 (27) B T 1/2 (28) 4 T 1/2 (29) B T 1/2 (30) 4T 1/2 (31) (Fig.…”
Section: Stimuli-responsive Spin State Switching In Mn(iii) Systemsmentioning
confidence: 77%
“…is at the forefront of a broad range of technological device applications, for example, in memory devices, [1][2][3][4][5][6][7] sensors, [8][9][10][11][12] displays, [13][14][15] telecommunication, 16,17 etc. The addressability of the physical and/or chemical properties as a response to external stimuli involves two distinct states (termed bistability) distinguishable by the appearance, particularly crystal shape and color, [18][19][20][21][22] optical properties, 23,24 magnetization, 25,26 electrical polarization, [27][28][29][30][31] electrical resistance, [32][33][34][35][36] dielectric constant, [37][38][39][40][41] or other interesting physical properties. The fine-tuning of molecular bistability requires (i) suitable electronic attributes via judicious tuning of the ligand field strength, [42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…[78][79][80][81][82][83][84][85][86][87] When considering recent results on fused [39][40][41][42]88 and magnetic porphyrins, 10,[44][45][46][47][48]89 together with the chemical structure/quantum coherence relationships reported in this article, these results demonstrate the suitability of magnetic porphyrin materials for quantum applications; the integration into single-electron transistors seems practicable, with the perspective to create molecular systems that can be used in single-molecule devices with magnetic control and electrical readout, and with potential applications in quantum information processing, as spin valves, or spin filters. 29,[86][87][88][89][90][91] The suppression of decoherence at low temperatures by molecular design is crucial because the magnetic states are very close in energy (usually < 1 meV), and thus, their electrical read-out is necessarily available only at temperatures below 10 K. 92,93 With that regard, extended materials based on P2•VO might offer an interesting platform, having a conduction channel available while keeping long phase memory times at low temperatures. These results constitute a fundamental step for the development of spin-electronic molecular quantum units.…”
Section: Discussionmentioning
confidence: 99%
“…6a,b). These devices were fabricated from electro-burnt graphene nanogaps, as described previously [47][48][49] . At room temperature (T = 300 K), the devices behave as field-effect transistors with a clearly observable bandgap and mild p-doping in most cases.…”
Section: Single-molecular Electronicsmentioning
confidence: 99%